Protective Effect of Quercetin against Paraquat-induced Brain Mitochondrial Disruption in Mice - Saberi-Hasanabadi, Parisa; Sedaghatnejad, Reza; Mohammadi, Hamidreza (Current Drug Safety, 2024)
Background: Paraquat is a highly toxic quaternary ammonium herbicide widely used in agriculture. It is an agent that induces pulmonary toxicity via the redox cyclic reaction. Objective: The present study investigated the protective effect of quercetin against paraquatinduced brain mitochondria disruption in mice. Methods: Paraquat (1.25 mg/kg, intraperitoneally) was administered to the mice, and then quercetin (50, 100, 200 mg/kg) was injected i.p. Oxidative damage biomarkers such as reactive oxygen species, protein carbonyl, lipid peroxidation, glutathione content, and mitochondrial function were assessed in the brain mitochondria. Results: The results showed that paraquat significantly (P < 0.001) increased the reactive oxygen species, protein carbonyl, and lipid peroxidation and significantly (P < 0.0001) decreased the glutathione content and mitochondrial function in the brain cells. Administration of the quercetin at doses of 50, 100, and 200 mg/kg significantly reduced reactive oxygen species, lipid peroxidation, and protein carbonyl and improved mitochondrial function and glutathione content in the mice brain mitochondrial compared to the paraquat group. Quercetin at 200 mg/kg dose had better effectiveness than 50 and 100 mg/kg doses. Conclusion: Our results suggest that quercetin in a dose-dependent manner has neuroprotective effects, probably by free radicals scavenging or enhancing the antioxidant mechanisms in the brain mitochondria. It seems that quercetin could modulate protein and lipid oxidation and improve oxidative damage induced by paraquat in the early stages.
Keywords: neuroprotective